Exploring the Challenges and Opportunities in Mental Health Care for Adolescents in Urban Indonesia - Cikita, Rafeni Bunga (Syntax Corporation Indonesia, 2025)
Mental health issues among adolescents in urban Indonesia are a growing concern, exacerbated by urbanization and socio-cultural factors. This research explores the challenges and opportunities in mental health care for adolescents in urban settings, specifically in cities like Jakarta, Surabaya, and Bandung. The study employs a mixed-methods approach, combining quantitative surveys of 300 adolescents and qualitative interviews to identify the prevalence of mental health disorders and the barriers to accessing care. The findings reveal a high prevalence of anxiety, depression, and stress, with significant gender differences—females reporting higher rates of anxiety and depression. The study also identifies key barriers, including cultural stigma, lack of awareness, and limited access to services, particularly for those from lower socioeconomic backgrounds. While existing interventions show promise, they are insufficient in addressing the specific needs of adolescents. The research emphasizes the importance of gender-sensitive, community-based mental health programs and the potential role of digital solutions in improving accessibility and reducing stigma. The study concludes with actionable recommendations for policymakers, mental health professionals, and educators to enhance adolescent mental health care in urban Indonesia.